TEA SAPONIN MODULATES IN VITRO RUMEN FERMENTATION PROFILE AND REDUCES METHANE PRODUCTION: A META-ANALYSIS - Yulianri Rizki Yanza; Nurhayatun Mahmudah; Cecep Hidayat; Anuraga Jayanegara; Ainissya Fitri; Fitri Ramadhani; Hindun Syarifah; Hasan Basri Jumin; Dedek Andrian; Melissa Melissa; Nurul Fauziah; Leo Adhar Effendi (BIOTROPIA, 2023)
Saponins are secondary plant metabolites binding hydrophobic non-sugar components that can reduce ruminant methane (CH4) production. Previous studies revealed that tea saponin is one of the common sources of saponins used to reduce enteric CH4 production. However, the effect of different levels of dietary tea saponin on rumen fermentation remains inconclusive. This study aimed to investigate the effect of tea saponin on in vitro rumen fermentation and methane production through a meta-analysis approach. A total of 6 articles were selected and included in the meta-analysis database, continued by the statistical analysis using SAS software through mixed model formula. The results showed that tea saponin levels lowered in vitro organic matter degradability (IVOMD) and in vitro dried matter degradability (IVDMD; P=0.01) by a linear response. Furthermore, increased tea saponin levels in the diet reduced enteric CH4 emission expressed as CH4/DM substrate and CH4/IVOMD by a quadratic (P=0.01) and a linear response (P=0.04), respectively. Increased tea saponin levels also tended to decrease gas production linearly (P=0.08). Tea saponins inclusion also decreased pH levels linearly (P=0.04) but increased NH3 quadratically (P=0.01). Moreover, total VFA concentration in the rumen also raised quadratically, followed by the increased acetate (C2) and propionate (C3) proportion by a linear response (P<0.05). As a result, the C2/C3 ratio was decreased in a linear response (P=0.01) by the increased tea saponin levels, where the protozoa population was also diminished by a quadratic response (P=0.01). In conclusion, tea saponin levels directly reduced enteric CH4 production by diminishing microbial populations.